Verbal fluency in Mexican Spanish-speaking subjects with high educational level: Ranking of letters and semantic categories - Reynoso-Alcántara, Vicenta; Silva-Pereyra, Juan; Vergara-Lope Tristán, Samana; Díaz Camacho, José Enrique; Guiot Vázquez, María Isabel; del Callejo Canal, Diana Donají; Canal Martínez, Margarita Edith (Journal of clinical and experimental neuropsychology, 2019)
Introduction: Verbal fluency tasks are useful tools in clinical practice and research studies across languages and contexts, but specific data obtained using Spanish phonological tasks and semantic tasks with different levels of difficulty are lacking. The present study aimed to determine the difficulty level of a phonological tasks and semantic tasks among Spanish-speakers. Method: Both tasks were ordered across five difficulty levels based on the frequency of use in Mexican Spanish (phonological) and the number of elements given by a group of participants (semantic). One hundred healthy Mexican Spanish-speaking participants (aged 24-63 years; 55 females) were presented with five phonological and five semantic categories. The participants also underwent a neuropsychological test and sociodemographic interview. The number of words correctly produced in each category within one minute was calculated. An ANOVA and a Kruskal-Wallis analysis were conducted in order to know if there were different levels of difficulty in the tasks. Additionally, correlation analyzes were performed to test the effect of the sociodemographic and cognitive variables on the participants' responses. Results: According to the analyzes, there were different levels of difficulty in the categories; P was the easiest and O was the most difficult category in the phonological tasks, and body parts and precious stones were the easiest and most difficult, respectively, in the semantic tasks. Age had a negative correlation with four-legged animals and a positive correlation with O; Positive correlations were also found between education and professions, vegetables, and alcoholic beverages; and between IQ and D, N, musical instruments, sports, vegetables, and trees. Conclusions: Both tasks offer categories with different level of difficulty based on the performance of a highly educated Mexican population. These data may be useful for clinical and research purposes.